Thermal degradation of heterogeneous plastic waste fractions: A hybrid DAEM & parallel reaction approach - Kartik, S.; Balsora, Hemant Kumar; Chakinala, Anand Gupta; Modi, Jigisha; Chin, Bridgid Lai Fui; Saptoro, Agus; Vinu, R.; Joshi, Jyeshtharaj B; Sharma, Abhishek (2024)
Assessment of polymer decomposition rates through kinetic estimations is crucial considering the design and operation of process reactor systems. This study experimentally analyses weight loss patterns of pure plastic components (LDPE, HDPE, PP and PS) to evaluate decomposition kinetics through iso-conversional methods. Activation energy estimate for thermal degradation of the polymers follow normal distribution with accuracy of estimated kinetic parameters established though best fit of isoconversional plots. Evaluated parameters are applied with first order Distributed activation energy model (DAEM) and linear mixing rule to predict decomposition rate of pure as well as mixed plastic fractions. DAEM model predicts the activation energy distribution for degradation of LDPE, HDPE, PP and PS as 256, 257, 209 and 159 kJ/mol as mean values. Rate predictions for mixed plastic fractions are compared with literature through lower statistical parameter values ( ) ranging from 1.49 × 10−5 - 9.21 × 10−6. Rate estimations for custom selected plastic combinations evaluated through developed approach specify dispersion of rate curves, represented through reduction in degradation temperature in the range of 15 – 60 °C characteristic of interactions. Further, study helps in predicting rate of any mixed plastic waste stream by minimizing experimentations, with seamless integration into commercial reactor design packages.